Aging Impairs Myogenic Adaptation to Pulsatile Pressure in Mouse Cerebral Arteries. Issue 4 (April 2015) - Springo, Zsolt; Toth, Peter; Tarantini, Stefano; Ashpole, Nicole M; Tucsek, Zsuzsanna; Sonntag, William E; Csiszar, Anna; Koller, Akos; Ungvari, Zoltan I
Stability of myogenic tone in middle cerebral arteries (MCA) is essential for adequate control over penetration of pressure waves into the distal portion of the cerebral microcirculation. Because the increased pulse pressure observed in advanced aging is associated with cerebromicrovascular injury, the effect of aging on myogenic response of mouse MCAs was determined. Aging did not affect the myogenic constriction in response to static increases in pressure, whereas it significantly impaired pulsatile pressure-induced myogenic tone. Impaired myogenic adaptation of MCAs to pulsatile pressure may allow high pressure to penetrate the distal portion of the cerebral microcirculation, contributing to microvascular damage.